Revitalization of Jongke Market in Surakarta: Juridical Analysis and Its Impact on Social, Economic, Environmental and Cultural Aspects - Tifany Zurah Wibawati; Nuria Siswi Enggarani (Universitas Muhammadiyah Surakarta, 2025)
Jongke Market in Surakarta, which has been operating since 1922, underwent revitalization in 2023 to overcome various problems, such as damaged physical conditions, slums, and frequent flooding. This study aims to analyze the juridical aspects of revitalization based on Law No. 26 of 2007, Minister of Trade Regulation No. 21 of 2021, and Surakarta Regional Regulation No. 1 of 2010, and evaluate its impact on social, economic, environmental, and cultural aspects. The method used is empirical juridical with primary data from interviews and observations, and secondary data from literature studies. The results show that the revitalization policy has fulfilled the existing legal provisions, especially in the aspects of spatial planning, management of trade facilities, and protection of traditional markets. From the social aspect, revitalization improves comfort, but changes the interaction patterns of traders and buyers. From an economic aspect, the competitiveness of the market increased, but the distribution of benefits is still uneven, especially for traders on the upper floors experiencing a decline due to accessibility. From the environmental aspect, revitalization contributed to improved hygiene and better waste management. From the cultural aspect, revitalization maintains the identity of traditional markets through the promotion of local products and cultural events. Therefore, further policies are needed that ensure market revitalization not only provides physical benefits, but also strengthens the welfare of traders as well as maintaining existing social, economic, environmental, and cultural values.